Problems In Managing Waqf Endowment Asset In Bogor Regency - Yumarni, Ani; Suhartini, Endeh; Sardiana, Anna (Universitas Islam Negeri Raden Intan Lampung, 2019)
This article examines the role and function of Nazhir (guardian of endowment) in the empowerment of waqf objects in the Legal District of Bogor Regency, West Java, Indonesia. The aim is to increase Nazir's professionalism in increasing the productivity of waqf assets to be able to provide maximum benefits to the general public (ummah) in a sustainable manner. In Bogor district, there are waqf assets in the form of land totaling 5,686 locations within land areas of 4,433,860 M2. With such a large number of waqf assets, if managed professionally, the waqf will certainly be able to bring the sustainability of the Ummah economy, especially the sustainability of education for the younger generation. However, as this study found, only a few Nazhirs in the Bogor Regency area who have begun to develop productive waqf assets. The majority of Nazirs still use the old pattern which is not conducive to the development of the productivity of waqf property. Therefore it is necessary to optimize the role and function of Nazhir through continuous coaching by the Indonesian Waqf Board (BWI). In the form of (1) meetings in the context of coaching, (2) training activities, and (3) socialization related to the latest regulations regarding the management of waqf objects.